(untitled) (Medical Forum Monthly, 2024)
Objective: To study the causes of death on Exhumation in Pakistan. Study Design: Retrospective observational study. Place and Duration of Study: This study was carried out at Forensic medicine Department BMC Banu, Saido Medical College Sawat, Baynzir District Hospital Rawalpindi and Baynzir District Hospital Abbottabad from Jan 2008 to 31 March 2014 Materials and Methods: 200 cases of exhumation were included in this study which were conducted approximately in six years and four months by the medical boards of Banu, Sialkot, Rawalpindi and Abbottabad. The data was taken on proforma with the permission of the authorities which was based on exhumation conducted in these districts. The data was analyzed for results. Cases of deceased where cause of death was determined either by external and internal examination or by histological examination / chemical analysis of viscerae were included in this study. Partially decomposed, advancedly decomposed or skeletonized bodies, with no internal or external injuries sufficient to cause death and histological and toxicological reports failing to reveal any abnormal findings, were also included in the study. Different variables of bodies e.g., sex, age, time of death & disinterment, corpse condition and burial site were analyzed using statistical package for social services (SPSS) version 13. Results: There were maximum cases of exhumation 60 cases (30 %) at the disinterment time of 5 – 8 months and there were minimum cases 13 (6.5 %) at the disinterment time more than 2 years. It was seen that in 59 cases of exhumation (29.5 %) the dead body was fresh, 89 cases (44.5) the dead body was partially decomposed, in 29 cases (14.4 %) the dead body was advancedly decomposed and in 23 cases the corpse were almost skeletonized. There were 143 cases (71.5 %) belong to rural area and 57 cases (28.5 %) belong to urban area. The maximum cases 100 (50 %) were of age group 31 – 40 years and minimum cases of exhumation 12 (6 %) were of age group more than 50 years. It was also seen that there were 173 (86.5 %) male dead bodies were exhumed and only 27 cases (13.5 %) were of female dead bodies. In this study there was the cause of death in 13 cases (6.5 %) due to Fire arm injury, 07 cases (3.5 %) due to stab wound of the trunk, 9 cases (4.5 %) due cut throat, 18 cases (0.9 % due to blunt injury of head and chest, 0.5 cases (2.5 %) due to poisoning, 06 cases (03 %) due to asphyxia and 142 cases (71.5 %) the cause of death was unascertained due to advance decomposition or almost skeltonized corpse. Conclusion: Delayed exhumation due to lengthy legal procedures involved in carrying out this process leading to decomposition of bodies, resulting in unascertainable cause of death. Early decomposition of bodies due to multiple reasons like hot climate, water logging and salinity, improper drainage of graveyards etc is a bar to ascertain cause of death